Investigating the Association between Palatal Rugae and Sagittal Malocclusion: A Clinical Study - Poorna Devadoss; Ramachandra Prabhakar; Umamaheshwari R.; Saravanan R.; Sagaya Mary Priya R.P.; SameeraY N.A. (Indian Journal of Forensic Medicine and Pathology, 2025)
Introduction: Palatal rugae are unique anatomical ridges located on the anterior hard palate, remaining stable throughout an individual’s life. In forensic odontology and orthodontics, they serve as key landmarks. The stability of palatal rugae, coupled with their resistance to change, suggests potential diagnostic value, especially in sagittal malocclusion classi𿿿ed as Class I, II, or III by Angle’s system. This study investigates the association between palatal rugae patterns and sagittal malocclusion, exploring whether their morphological characteristics can aid in malocclusion diagnosis. Objectives: To examine whether palatal rugae patterns (length and width) are signi𿿿cantly associated with sagittal malocclusions (Class I, II, and III) andtoassesstheir potential role as non-invasive diagnostic tools for orthodontic assessment. Methodology: This cross-sectional clinical study involved 300 participants, aged 18 to 28, divided equally into three groups based on untreated sagittal malocclusion: Class I, Class II, and Class III, according to Angle’s classi𿿿cation. Strict inclusioncriteria ensured participants had no history of orthodontic treatment, systemic diseases, facial trauma, or habits affecting palatal anatomy. Pre-treatment maxillary dental models were made using high-quality alginate impressions and dental stone casts, focusing on primary palatal rugae for analysis. Key parameters measured were the mesio-distal (MD) length and anterio-posterior (AP) width of the rugae, with data collected using digital calipers. Statistical analysis was conducted with SPSS Ver 26.0, employing ANOVA to compare rugae dimensions between malocclusion groups, and Pearson Correlation Coef𿿿cient to assess the relationshipbetween rugae patterns and malocclusion. A signi𿿿cance level of p<0.05 was set. Results: The paired sample t-test results revealed no statisticallysigni𿿿cant difference in palatal rugae dimensions before and after orthodontic treatment across the regions studied (right and left medial and lateral rugae). For mesiodistal (MD) measurements, the mean difference for right-side rugae ranged from -0.0487 to 0.07806, while left-side rugae differences ranged from -0.0842 to 0.0837, with p-values consistently greater than 0.05. Similarly, for anterio-posterior (AP) measurements, the mean difference ranged from -0.0601 to 0.2622 across both sides, with no signi𿿿cant p-values observed. These𿿿ndings con𿿿rm hat palatal rugae atterns remained stable post-treatment, indicating no measurable changes in their dimensions. Conclusion: Palatal rugae patterns are not signi𿿿cantly associated ith agittal malocclusion, and their dimensions remain stable following orthodontic interventions. They can serve as reliable anatomical landmarks in orthodontics and forensic identi𿿿cation, offering potential for non-invasive diagnostics in linical settings.